2022
DOI: 10.1093/mnras/stac592
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous transit timing analyses of 10 exoplanet systems

Abstract: We study the transit timings of 10 exoplanets in order to investigate potential Transit Timing Variations (TTVs) in them. We model their available ground-based light curves, some presented here and others taken from the literature, and homogeneously measure the mid-transit times. We statistically compare our results with published values and find that the measurement errors agree. However, in terms of recovering the possible frequencies, homogeneous sets can be found to be more useful, of which no statisticall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 101 publications
0
5
0
1
Order By: Relevance
“…The exoplanet has a high equilibrium temperature of 1900 K, a moderate surface gravity of 10 m s −2 and completes a full orbit in 2.1 days. A search for transit timing variations from archival, published and new data by Baştürk et al (2022) revealed no trends of any kind to the time of mid-transit consistent with a stable orbit.…”
Section: The Wasp-74 Systemmentioning
confidence: 95%
See 1 more Smart Citation
“…The exoplanet has a high equilibrium temperature of 1900 K, a moderate surface gravity of 10 m s −2 and completes a full orbit in 2.1 days. A search for transit timing variations from archival, published and new data by Baştürk et al (2022) revealed no trends of any kind to the time of mid-transit consistent with a stable orbit.…”
Section: The Wasp-74 Systemmentioning
confidence: 95%
“…Motivated by the potential of this technique, we performed a search for the blue-optical increase of the planet radius during the transit of exoplanet WASP-74b. The WASP-74 system (Hellier et al 2015;Mancini et al 2019;Garhart et al 2020;Luque et al 2020;Baştürk et al 2022) consists of an F9 dwarf star with a mass of ∼1.3 M and a radius of ∼1.5 R and an inflated hot Jupiter with a mass of ∼0.9 M Jup and a radius of ∼1.4 R Jup . The host star has an effective temperature of ∼6000 K and a metallicity of ∼0.4 (Sousa et al 2021).…”
Section: The Wasp-74 Systemmentioning
confidence: 99%
“…Exoplanet host star XO-2 has been observed within a research program 1 that investigates the transit timing variations with a similar fashion given in Baştürk et al (2022). During these observations, variability of one of the comparison star in the field was noticed.…”
Section: Ccd Observationsmentioning
confidence: 97%
“…Exoplanet host star XO-2 has been observed within a research program that investigates the transit timing variations with a similar fashion given in Baştürk et al (2022). During these observations, variability of one of the comparison star in the field was noticed.…”
Section: Ccd Observationsmentioning
confidence: 98%